Le curriculum en actes révélé par les gestes didactiques de métier : étude des pratiques didactiques d'un enseignant débutant en EPS - Fabienne Brière-Guenoun (Université de Provence, 2014)
This research aims to account for the dynamics of the curriculum in acts through an analysis of "gestes didactiques de métier" of a physical education student teacher. It concerns the ways in which the teacher leads the study of knowledge in the didactic interaction in two lessons at different times of the year. The method connects video and interview data. Comparative analysis of the student teacher's gesture during two lessons shows differences which are attributed to the specificity of physical activities and the affirmation of the teacher's style over experience. Beyond, the results show a personal reappropriation by the teacher of institutional and cultural preconstructed in the joint action. Theoretical and methodological choices made in order to study the implementation of curriculum are finally discussed.